Diurnal Spikes of Intraocular Pressure in Uveitic Glaucoma: A 24-hour Intraocular Pressure Monitoring Study - ÇERMAN, EREN; ÇELİKER ATABERK, HANDE; ERASLAN, MUHSİN (TAYLOR & FRANCIS INC, 2020)
Purpose The aim of this study was to document diurnal changes in intraocular pressure (IOP) in uveitic glaucoma (UG) and compare it with primary open angle glaucoma (POAG) patients. Methods Eight patients with UG and seven patients with POAG were included in this study. The patients were matched for age, gender, and glaucoma medications. None of the patients experienced angle closure, uveitis attack, and ocular surgery, and were not under steroid or immunomodulatory therapy within the last three months. The 24-hour IOP fluctuations were recorded with the help of a contact lens sensor (Sensimed Triggerfish (R), Switzerland). The diurnal IOP fluctuations were modeled with best-fit lines and statistical comparisons between the longitudinal responses of the two groups were determined with nonlinear regression. Results The comparison of mean 24-hour contact lens sensor (CLS) amplitudes revealed a significant difference between the fluctuation levels of UG and POAG groups (213 +/- 160 millivolt equivalents (mVeq) vs. 162 +/- 168 mVeq, respectivelyp= .003). The top level of the best-fit curves was significantly higher in the UG group (266 +/- 143 mVeq) compared to the POAG group (159 +/- 162 mVeq,p< .001). Both curves had their top levels between 5:00 PM and 8:00 AM. The longitudinal regression analysis revealed that the amplitudes of the 24-hour fluctuation waves were significantly different (p= .041). Conclusions This study demonstrated for the first time that the diurnal variation in IOP was significantly higher in UG patients. This difference was also more distinct between 5:00 PM and 8:00 AM clock-hours. The uveitis and glaucoma specialists should consider this potential for higher IOP fluctuations, while tailoring the glaucoma treatment in uveitic patients.
Keywords: Contact lens sensor; diurnal fluctuation; nocturnal fluctuation; uveitic glaucoma; 24-hour intraocular pressure monitoring; PRIMARY OPEN-ANGLE; PATTERNS; FLUCTUATIONS; PROGRESSION